A Retrospective Audit of Clinically Significant Maternal Bacteraemia in a Specialist Maternity Hospital from 2001 to 2014. (1st October 2015) - Drew, Richard John; Fonseca-Kelly, Zara; Eogan, Maeve
Abstract : Maternal sepsis is a significant problem in obstetrics, with almost one in four maternal deaths related to severe sepsis. We carried out a retrospective review of clinically significant bacteraemia in obstetric patients attending Rotunda Hospital over 14 years. From 2001 to 2014, there were 252 clinically significant positive blood culture episodes in obstetric patients. There were 112, 361 live births >500 g during the study period giving an overall rate of 2.24 clinically significant positive maternal blood culture episodes per 1000 live births >500 g. The median rate over the 14 years was 2.12 episodes per 1000 live births >500 g, with an interquartile range of 1.74–2.43 per 1000 live births >500 g. There was no discernable increasing or decreasing trend over the 14 years. E. coli was the most commonly isolated organism ( n = 92/252, 37%), followed by group B Streptococcus ( n = 64/252, 25%), Staphylococcus aureus ( n = 28/252, 11%), and anaerobes ( n = 11/252, 4%). These top four organisms represented three-quarters of all positive blood culture episodes ( n = 195/252, 77.3%). Of note, there were only five cases of listeriosis, representing a rate of 4.4 cases per 100, 000 live births >500 g. The rate of invasive group A streptococcal infection was also very low at 5.3 cases per 100, 000 live births >500 g.